The Saga of the Volsungs : the Norse epic of Sigurd the Dragon Slayer - Byock, Jesse L. (University of California Press, 2012)
The Saga of the Volsungs is an Icelandic epic of special interest to admirers of Richard Wagner, who drew heavily upon this Norse source in writing his Ring Cycle and a primary source for writers of fantasy such as J.R.R. Tolkien and romantics such as William Morris. A trove of traditional lore, it tells of love, jealousy, vengeance, war, and the mythic deeds of the dragonslayer, Sigurd the Volsung. Byock's comprehensive introduction explores the history, legends, and myths contained in the saga and traces the development of a narrative that reaches back to the period of the great folk migrati.